Ibn Hishām’s Methodology in His Commentary on Alfiyyat Ibn Mālik in the Book Auḍaḥ al-Masālik ilā Alfiyyat Ibn Mālik - Hidayati, Sri Erna; Asrina, Asrina; Hadi, Syofyan (UIR Press, 2026)
Abstract The central issue of this study is to examine Ibn Hishām’s methodology in his commentary on Alfiyyat Ibn Mālik in his book Auḍaḥ al-Masālik ilā Alfiyyat Ibn Mālik. The purpose of this research is to clarify Ibn Hishām’s methodological approach in explaining Alfiyyat Ibn Mālik in Auḍaḥ al-Masālik ilā Alfiyyat Ibn Mālik. The research method employed is library research. The findings indicate that Auḍaḥ al-Masālik encompasses all the chapters of the Alfiyyah. Ibn Hishām revised the formulation of certain sections, modifying some chapter titles solely for the sake of clarification, and then reorganized their subjects into subchapters after they had originally been presented as main chapters. He rarely cited the verses of the Alfiyyah, except when necessary, such as when he intended to object to or disagree with the author. The commentator began some sections with technical definitions and brief explanations, considering that certain chapter titles were ambiguous and required clarification to provide a general overview of the topic. However, he did not do so when there was no need. Ibn Hishām’s sources of evidence in Auḍaḥ al-Masālik include the Qur’an, Prophetic hadiths, and Arabic poetry. His stance toward grammatical differences ranged between support and rejection. Thus, Auḍaḥ al-Masālik serves as a clarification of the content of the verses of Alfiyyat Ibn Mālik, rather than a direct line-by-line commentary on its verses as undertaken by other commentators of the Alfiyyah. Keywords: Ibn Hishām, Alfiyyat Ibn Mālik, Auḍaḥ al-Masālik ilā Alfiyyat Ibn Mālik, Ibn Mālik.